3
$\begingroup$

How do you evaluate $$\prod_{n=1}^{\infty}\left(1+\frac{1}{n^2}+\frac{1}{n^4}\right)$$ using the identity $$\sin(\pi z)=\pi z\prod_{n=1}^{\infty}\left(1-\frac{z^2}{n^2}\right)?$$

I assume I'll have to express $1+\frac{1}{n^2}+\frac{1}{n^4}$ as $\left(1+\frac{a}{n^2}\right)\left(1+\frac{b}{n^2}\right)$ for some $a,b\in\mathbb{C}$ so that I could use the identity given, but I can't seem to factor the above appropriately.

$\endgroup$
  • $\begingroup$ I checked wolframalpha and it is indeed convergent with limit 5.89611... $\endgroup$ – Dante May 17 '17 at 7:33
  • 2
    $\begingroup$ In your identity, you can choose $a = (1+i\sqrt{3})/2$, $b = (1-i\sqrt{3})/2$. $\endgroup$ – Rigel May 17 '17 at 7:35
  • $\begingroup$ @Rigel WOW it worked. How on earth did you figure that factorization out? $\endgroup$ – Dante May 17 '17 at 7:38
  • 5
    $\begingroup$ Once you write $1+\frac{1}{n^2}+\frac{1}{n^4} = (1+\frac{a}{n^2})(1+\frac{b}{n^2})$, you see that you must have $a+b=1$, $ab = 1$ and then you solve this system (or you observe that $a$, $b$ are the solutions of the equation $z^2-z+1=0$). $\endgroup$ – Rigel May 17 '17 at 7:42
  • 2
    $\begingroup$ @Rigel I advise you to group your comments into an answer. I will surely upvote it. $\endgroup$ – Jean Marie May 17 '17 at 8:02
2
$\begingroup$

We have $1+z+z^2=\Phi_3(z)=(z-\omega)(z-\bar{\omega})=(1-\omega z)(1-\bar{\omega}z)$, with $\omega=\exp{\frac{2\pi i}{3}}$.
By considering $z=\frac{1}{n^2}$ and $\eta=\exp\frac{\pi i}{3}$ we have that $$ \frac{\sin(\pi w)}{\pi w}=\prod_{n\geq 1}\left(1-\frac{w^2}{n^2}\right)\tag{1} $$ implies: $$ \prod_{n\geq 1}\left(1+\frac{1}{n^2}+\frac{1}{n^4}\right) = \frac{\sin(\pi\eta)\sin(\pi\bar{\eta})}{\pi^2}=\frac{\cos(\pi(\eta-\bar{\eta}))-\cos(\pi(\eta+\bar{\eta}))}{2\pi^2}\tag{2}$$ so that: $$ \prod_{n\geq 1}\left(1+\frac{1}{n^2}+\frac{1}{n^4}\right) = \color{red}{\frac{1+\cosh(\pi\sqrt{3})}{2\pi^2}}=\left(\frac{1}{\pi}\,\cosh\frac{\pi\sqrt{3}}{2}\right)^2.\tag{3}$$

$\endgroup$
4
$\begingroup$

Observing that $$ \left(1+\frac1{n^2}+\frac1{n^4}\right) =\left(1-\frac{a^2}{n^2}\right)\left(1-\frac{b^2}{n^2}\right) $$ where $$ a^2+b^2=-1\\ a^2b^2=1 $$ find $a$ and $b$ by a direct computation.

We get

\begin{align*} \prod_{n\ge1}\left(1+\frac1{n^2}+\frac1{n^4}\right) =&\prod_{n\ge1}\left(1-\frac{a^2}{n^2}\right)\left(1-\frac{b^2}{n^2}\right)\\ =&\prod_{n\ge1}\left(1-\frac{a^2}{n^2}\right) \prod_{n\ge1}\left(1-\frac{b^2}{n^2}\right)\\ =&\frac{\sin(\pi a)}{\pi a}\frac{\sin(\pi b)}{\pi b} \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.